Getting all the facts of death - Elsie H. Burger; Jimmy Volmink (South African Family Practice)
We conducted a study of death notification form (DNF) completion relating to 844 deceased Cape Town residents, and evaluated the completeness of information on the forms. The DNFs frequently lacked important data on both the deceased and the health professional who completed the DNF (completing health professional). Urgent intervention is needed to improve the usefulness of the DNF as a source data on health statistics in South Africa.